Roasting process shaping the chemical profile of roasted green tea and the association with aroma features. (15th August 2021) - Zhu, Yu-Meng; Dong, Jun-Jie; Jin, Jing; Liu, Jin-Hua; Zheng, Xin-Qiang; Lu, Jian-Liang; Liang, Yue-Rong; Ye, Jian-Hui
Highlights: Both FIR and drum roasting treatments reduced flavonoids but increased volatiles. FIR irradiated and drum roasted teas were distinguished by flavonoid compositions. FIR irradiated and drum roasted teas had different aroma features. WGCNA showed 56 volatiles were correlated with the aroma traits of roasted teas. Aldehydes, ketones, furans and pyrroles/pyazines increased during roasting. Abstract: Roasting process impacts the chemical profile and aroma of roasted tea. To compare the impacts of far-infrared irradiation and drum roasting treatments (light, medium and heavy degrees), the corresponding roasted teas were prepared from steamed green tea for chemical analyses and quantitative descriptive analysis on aroma, and correlations between volatiles and aroma attributes were studied. There were 8 catechins, 13 flavonol glycosides and 105 volatiles quantified. Under heavy roasting treatments, most catechins and flavonol glycosides decreased, and aldehydes, ketones, furans, pyrroles/pyrazines, and miscellaneous greatly increased, while far-infrared irradiated teas had distinct nutty aroma compared with the roasty and burnt odor of drum roasted teas. The weighted correlation network analysis result showed that 56 volatiles were closely correlated with the aroma attributes of roasted teas. This study reveals the differential chemical and sensory changes of roasted teas caused by different roasting processes, and provides a novel way for flavor chemistry study.